Contact line behavior on nanoporous alumina surfaces. Issue 4 (1st December 2013) - Bokalawela, Roshan S. P.; Awitor, Komla O.; Massard, Christophe; Raspal, Vincent; Johnson, Matthew B.
Abstract : The aim of this study is to describe the behavior and the thickness of a three-phase system contact line on nanoporous alumina surfaces based on wetting hysteresis measurements. The nanoporous alumina templates were fabricated by anodization of aluminum foil in an oxalic or sulfuric acid solution. The oxide film consists of a well-ordered hexagonal array of pores with uniform diameter. The morphology was controlled by varying the pore diameter, depth and spacing. The wetting behavior of the nanoporous alumina templates was investigated using advancing and receding contact angle measurements carried out by varying the volume of the water droplets used. The surfaces showed a large hysteresis, with a receding contact angle always equal to zero making them strongly adhesive despite their hydrophobicity. Comparing linear and areal models indicates that the contact line thickness is negligible compared with the size of the nanopores. Contact line pinning highlights the role of the surface shape around the pores in the marked adhesive behavior of our templates.